IMPLEMENTASI ALGORITMA KNUTH-MORRIS-PRATT MENGGUNAKAN METODE STRING MATCHING PADA APLIKASI E-ARSIP INAKTIF BALAI BESAR PELATIHAN VOKASI DAN PRODUKTIVITAS (BBPVP) KOTA SERANG - Sutanto Sutanto; Checka Bahtera (Journal of Innovation And Future Technology, 2025)
Every governmental organization needs a data and information source, and one such source is an archive. The Serang Vocational and Productivity Training Center (BBPVP) functions as a technical implementation unit under the Directorate General of Vocational and Productivity Training Development within the Ministry of Manpower of the Republic of Indonesia. During activities at the Serang Vocational and Productivity Training Center (BBPVP), information sources in archives were utilized; however, issues arise regarding the management of borrowed archives that have not been effectively organized. This mismanagement increases the risk of archives being lost as they are not returned after borrowing, particularly for older archives, which are also at risk of damage due to improper storage locations in the documents. Storage or because of calamities like floods and fires. The methodology employed in the data processing system involves methods of data collection, including literature review, observation, and interviews. This application is developed utilizing UML modeling, or Unified Modeling Language. The approach adopted in creating this application is the waterfall model, which follows a series of phases beginning with requirements analysis, followed by system design, implementation, integration and testing, and finally operation and maintenance.